WORLD-VIEW AND FORMATIVE POTENTIAL OF PHILOSOPHICAL KNOWLEDGE IN THE SYSTEM OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE FIELD OF SOCIAL WORK (Psychology Travelogs, 2024)
The article examines the role of philosophical knowledge in the formation of the personality of a higher education student - a future social work specialist, whose professional activity in the future is associated with the current problems of society, social security of population groups and specific individuals in need of help. It is noted that an important factor in the development of higher education in Ukraine is the improvement of the methodology of teaching social and humanitarian disciplines, in particular philosophy. Philosophical knowledge in the system of professional training of specialists is defined as not only the sum of humanitarian knowledge, but also a special state of mind and intellect, which determines the desire for free critical thinking. The emphasis is on the fact that it is philosophy that provides a realistic perception of social life in its individual manifestations and forms the scientific worldview, value orientations and life positions of a higher education student - a future professional.The main aspects of the problem of forming the worldview of future specialists by means of philosophy are determined: (1) the content of educational material on philosophy should be consistent with the specialization of students; (2) higher education applicants must be ready to perceive the problematic field of philosophy; (3) the implementation of philosophy must acquire an innovative interactive character; (4) the educational component of courses in the specialty "Social Work" must include social philosophy and related disciplines for the development of students' analytical abilities; (5) higher educational institutions must prepare not only educated, but also spiritual, highly moral individuals - the moral elite of the state.The paper concludes that for the formation of the personality of a future social work specialist, whose future professional activity will be associated with current problems of society, the worldview-forming potential of philosophical knowledge is of particular importance, philosophy forms the scientific worldview, value orientations and life positions of the future professional, and therefore is the basis for the humanization of the entire system of modern higher education.
Keywords: philosophical knowledge; social work; scientific worldview; value orientations; moral elite of the state